2017
DOI: 10.1080/21580103.2017.1349003
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of degraded forest ecosystem through non-forestry livelihood supports: experience from the Chunati Wildlife Sanctuary in Bangladesh

Abstract: Lack of non-forestry income sources for the forest-dependent community was one of the major causes of continued biodiversity loss in Chunati Wildlife Sanctuary (CWS). A livelihood support program was implemented from July 2012 through June 2015 to reduce people's forest-dependence for their livelihoods. We evaluated the efficacy of this program in enhancing the biodiversity health of CWS. An Ordinary Least Square regression framework was used to estimate the difference in difference of the income between the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 9 publications
(8 reference statements)
0
11
1
Order By: Relevance
“…3) which indicate that the continuity of vegetation varies signi cantly from one place to another. However, all these values were considerably higher than that obtained from different studies on the natural forests of Bangladesh [70][71][72][73][74][75][76] . One of the probable reasons behind this phenomenon is that, natural forests are well-stablished ecosystem sustaining over a long time while vegetations of abandoned mansions are comparatively recent establishments via secondary succession of plant species.…”
Section: Discussioncontrasting
confidence: 67%
“…3) which indicate that the continuity of vegetation varies signi cantly from one place to another. However, all these values were considerably higher than that obtained from different studies on the natural forests of Bangladesh [70][71][72][73][74][75][76] . One of the probable reasons behind this phenomenon is that, natural forests are well-stablished ecosystem sustaining over a long time while vegetations of abandoned mansions are comparatively recent establishments via secondary succession of plant species.…”
Section: Discussioncontrasting
confidence: 67%
“…However, the result of this study showed that the biodiversity status and forests stock condition of community managed forests is still in better condition than other government managed forests in Bangladesh. Hossain et al (2013), Hossain, Hossain, Alam, and Uddin (2015), , Rahman et al (2011), and Rahman et al (2017Rahman et al ( , 2016 conducted different studies in different government managed forests throughout the country to calculate phytosociological attributes and biodiversity indices. Findings of these studies showed the poor diversity than our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Basak et al (2014) found a total of 148 plant species belonging to 128 genera under 61 families from a VCF covering only 20 ha area. These findings are the testimony that the biodiversity status of VCFs is still better than the government managed forests (Hossain, Hossain, Salam, & Rahman, 2013;Rahman et al, 2011;Rahman, Mahmud, & Ahmed, 2017;Rahman, Mahmud, Shahidullah, Nath, & Jashimuddin, 2016).…”
Section: Introductionmentioning
confidence: 91%
“…Consequently, conflict arises between local people and the Forest Department. The former use the forestland for their livelihood, and the latter seek to restrict the forestland’s use for biodiversity conservation (Rahman et al 2017a ).…”
Section: Methodsmentioning
confidence: 99%
“…The CWS is one of the pilot sites in Bangladesh for co-management project implementation with financial and technical assistance from the United States Agency for International Development (USAID), in partnership with the Forest Department (Rahman 2013 ). Between 2004 and 2018, three co-management projects have been implemented in this sanctuary, aiming to restore, protect and conserve the remaining forest biodiversity, undertake sustainable use of forest resources and reduce forest dependency among forest-dependent communities through alternative income-generating (AIG) activities (Rahman et al 2017a , b ). Furthermore, the Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ)-funded Management of Natural Resources and Community Forestry (MNRCF)-Chunati project (2009–2015) implemented pilot reforestation and sustainable forest management measures in CWS based on cooperation between local co-management organisations and the Forest Department.…”
Section: Methodsmentioning
confidence: 99%